An Investigation on the Readiness of the Sri Lankan Construction Industry towards Internet of Things (IoT): Conceptual Guideline - Dilakshan, S.; Rathnasinghe, A.P.; Seneviratne, L.D.I.P. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2021)
The world is witnessing the dawn of the Fourth Industrial Revolution known as Industry 4.0, where the ICT-fuelled digital economy is taking off exponentially. In such a context, the essence of the Internet identified as the Internet of Things (IoT) is a revolutionary way of procuring goods and services. IoT refers to scenarios where network connectivity and computing capability extend to objects, sensors, and everyday items not generally considered as computers while allowing them to interact among each other with the least involvement of humans. The application of IoT has already extended to the sectors such as manufacturing, transportation, energy, retail, smart cities, healthcare, and buildings to significantly improve the quality of life by increasing efficiency, productivity, profitability, and innovation.
Keywords: Internet of Things (IoT), Industry 4.0, Construction Informatics, Information Technology, Smart Sensors